2022
DOI: 10.48161/qaj.v2n1a90
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the COVID-19 on Our Daily Lives in Bangladesh

Abstract: The COVID-19 pandemic originated from Wuhan, China, spread around the world with horror and dramatic loss of human life. The economic and social catastrophe has made it even more irresistible. An attempt has been made to find out what kind of psychological and livelihood-related impacts Covid-19 has had on our daily lives. Data had been collected through convenient online surveys where 344 respondents were interviewed. Most of the respondents reported the reduction of movement, income and working hours. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…In contrast to the quantity of time spent on indoor sporting activities, were somewhat increased. On the contrary, Pitol et al ( 2022 ) found the opposite result in Bangladesh. Moreover, religious activities, BMI, Internet shopping, sleeping time, anxiety, caffeine consumption, medical consumption, watching movies, and watching drama series increased slightly during COVID-19.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…In contrast to the quantity of time spent on indoor sporting activities, were somewhat increased. On the contrary, Pitol et al ( 2022 ) found the opposite result in Bangladesh. Moreover, religious activities, BMI, Internet shopping, sleeping time, anxiety, caffeine consumption, medical consumption, watching movies, and watching drama series increased slightly during COVID-19.…”
Section: Discussionmentioning
confidence: 92%
“…The most alarming thing was that Generation –Z was addicted to the virtual world, like online games (PUBG., free fire, Clash of Clans, etc. ), movies, dramas, Facebook, YouTube, and so on (Pitol et al 2022 ). The condition was more severe during the COVID-19 lockdown due to academic delay (Agnew et al 2019 ) and uncertain careers (Sahu 2020 ) for Generation Z.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most alarming thing was that Generation -Z was addicted to the virtual world, like online games (PUBG., free re, Clash of Clans, etc. ), movies, dramas, Facebook, YouTube, and so on(Pitol et al 2022). The condition was more severe during the COVID-19 lockdown due to academic delay(Agnew et al 2019) and uncertain careers(Sahu, 2020) for Generation Z.However, the professional expeditions were somewhat reduced, and a decrease followed in time spent participating in outdoor activities.Foo et al (2020) and Harris et al (2022) explored that the execution of MCO and CMCO caused the revocation of many professional trips and outdoor activities and introduced work-from-home lifestyles.…”
mentioning
confidence: 99%